Pengembangan Program Pelatihan TIK bagi Guru Pendidikan Agama Islam dalam Meningkatkan Keterampilan Menggunakan Media Pembelajaran di Sekolah Menengah Atas Negeri 6 Palembang - M. Robbani (Bahasa Indonesia, Bahasa English, 2019)
An increasingly uncertain future with a variety of challenges to be faced has wide and profound implications for a variety of teaching designs and learning techniques. This is not only related to teacher competence to be able to educate, but how teachers are able to use/utilize learning media based on Information and Communication Technology (ICT) in teaching and learning activities. Therefore this study aims to; produce ICT training programs for Islamic education teachers in improving skills using instructional media in Palembang 6 Public High School and assess the effectiveness of ICT training programs for Islamic education teachers in improving skills using learning media in Palembang 6 Public High School. The average posttest score was 81.67 and the pretest value was 53.33, there was a difference in value of 28.33. Then the t value is -8,500 with sig <0.05 (0.014 <0.050). After comparing with the significance level of 5%, there is a significant difference in the improvement of the skills of Islamic religious education teachers in Palembang 6 Public High School in using IT-based learning media.